Prevalence of malnutrition and its associated factors among 6-59 months children attending the pediatric outpatient department in a tertiary care center in rural Nepal - Shrestha, Sandeep; Pant, Prem Prasad; Gautam, Uttara; Thani, Kamal Prasad; Shrestha, Annie; Keshari, Munna; Sainju , Akina; Lamichhane , Santosh; Yadav , Lokendra Kumar; Rana, Elisha (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Children constitute the most vulnerable group of any community. Their nutritional status is a sensitive indicator of community health and nutrition. Malnutrition is a very common problem in children under five years of age in Nepal and is a significant contributor to mortality and morbidity accounting for more than half of all child deaths. This study was done to assess the burden of malnutrition and associated factors among children aged 6-59 months.Methods: This was a hospital based cross-sectional study, conducted from June 2022 to May 2023 at the Pediatrics OPD of Karnali Academy of Health Sciences (KAHS), Jumla. A total of 164 children were enrolled for this study. Anthropometric measurements were used as per WHO guidelines to asses three nutritional status: Underweight, stunting, and wasting using descriptive statistics and chi square test were applied using SPSS 16 to assess social and predisposing factors. All the data were recorded in the preformed proforma. It was then, analyzed with the help of SPSS version 16. p-value< 0.05 was considered statistically significant.Results: Prevalence of stunting, wasting, and underweight were 38.4%, 39.1%, and 39.7% respectively. The prevalence of stunting and underweight was seen more in males than in females whereas wasting was very similar in both sexes.Conclusion: The findings showed that there is high prevalence of malnutrition in Jumla, so monitoring of nutrition status in children should be taken seriously and needs to be addressed.